2020
DOI: 10.1177/1120672120922444
|View full text |Cite
|
Sign up to set email alerts
|

Statin reduces the incidence of diabetic retinopathy and its need for intervention: A systematic review and meta-analysis

Abstract: Purpose: We aimed to perform a systematic literature search on the latest evidence of the role of statin in reducing diabetic retinopathy and its need for intervention. Methods: A comprehensive search on cohort studies/clinical trials that assess statins and diabetic retinopathy up until August 2019 was performed. The outcome measured was the incidence of diabetic retinopathy and its need for intervention. Results: There were 558.177 patients from six studies. Statin was associated with a lower incidence of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
1
18
0
1
Order By: Relevance
“…More recently in 2020, Pranata et al performed a systematic literature search and demonstrated that statin treatment was strongly correlated with a remarkably decreased risk of diabetic retinopathy. Moreover, statin treatment also lowered the necessary for the therapy with intravitreal injection and vitrectomy [44]. Similar conclusions could also be seen in another study which aimed to assess the function of lipid-lowering agents on diabetic retinopathy and its related complications requiring intervention [45].…”
Section: Statinssupporting
confidence: 63%
“…More recently in 2020, Pranata et al performed a systematic literature search and demonstrated that statin treatment was strongly correlated with a remarkably decreased risk of diabetic retinopathy. Moreover, statin treatment also lowered the necessary for the therapy with intravitreal injection and vitrectomy [44]. Similar conclusions could also be seen in another study which aimed to assess the function of lipid-lowering agents on diabetic retinopathy and its related complications requiring intervention [45].…”
Section: Statinssupporting
confidence: 63%
“…A search for a safer systemic approach to preventing or delaying development of complications has re-examined the benefits of the lipid-lowering drug fenofibrate ( 223 , 224 ), but the, albeit uncommon, side-effects have also prevented its widespread use. Experience with the liberally prescribed statins has also been examined as a possible means of eliminating the hyperlipidemic risk factor for DR, and there is some evidence from RCT’s ( 225 227 ) but a critical analysis of published data suggests that the quality and reporting of the data may be flawed ( 228 ). Experimentally, rosuvastatin has been shown to inhibit leukostasis in which the effect appeared to act on the endothelium rather than the leukocytes, thus pointing to a primary metabolic defect in the endothelium initiating leukostasis ( 145 ).…”
Section: Preventing and Treating The Microvasculopathy Of Obesity/thementioning
confidence: 99%
“…The FIELD study 12) showed HDL-C, LDL-C, and TG levels were not the significant markers for laser treatment. However, fibrate 12) and statin 36) intake was shown to reduce the need for laser treatment in randomized controlled trial and metaanalysis. Taken together, there might be a weak or borderline association between LDL-C and the risk for diabetic retinopathy.…”
Section: Lipid Markers For Predicting the Need For Laser Treatmentmentioning
confidence: 99%